Complications in surgical management of calcaneal fractures with anatomical plates - Quadri, Asfia; Vasif, M. Zeeshan (International Journal of Research in Orthopaedics, 2021)
Calcaneal fractures, irrespective of their types, are treated non-operatively, one of the reasons being fear of complications. But conservatively managed fractures can result in equally problematic complications. Incidence of subtalar arthritis in such cases is reported to be 16.9% compared 3.3% in cases treated surgically. With surgical treatment aimed at achieving anatomical joint reduction, regaining calcaneal height, its length and width, successful attempts at curtailing the long-term complications can be made. This was a prospective study of 20 cases of calcaneal fractures, admitted to MNR Medical College and Hospital, Sangareddy from August 2020 to September 2021 were treated with ORIF with non-locking anatomical calcaneal plates using Fernandez’s approach, without use of bone graft. Essex Lopresti and Sander’s classification were used. Intra-operative assessment of reduction and articular surface reconstruction was done under fluoroscopic guidance. Regular follow up was done for assessment of fracture union and complications, assessment of late collapse. Among the 20 cases, 73% were men and 27% women. On typing the fractures based on Essex-Lopresti classification, intra-articular tongue type constituted 13% and 87% were of joint depression. Near normal anatomical reduction was obtained in all cases except in one where it was difficult due to comminution noted during surgery. 2 cases developed superficial skin necrosis at the surgical site, 1 case of deep infection and abscess formation and 3 cases of subtalar arthritis. This study showed that the incidence of long-term complications can probably be minimized by restoring the altered anatomy through surgical means; hence we advocate surgical management and accurate anatomical reduction in cases of displaced and comminuted calcaneal fractures with proper surgical principles.